2023
DOI: 10.3389/fpubh.2023.1170612
|View full text |Cite
|
Sign up to set email alerts
|

The elderly's satisfaction with physical activity programs in senior welfare centers

Abstract: IntroductionHealthcare for the aging population has become a crucial issue in South Korea to maintain the elderly's quality of life, and physical activity is of primary importance for older adults. This study evaluated the exercise characteristics and satisfaction of the elderly who participated in physical activity programs provided by senior welfare centers in South Korea.MethodsWe surveyed 266 participants to learn the characteristics of the elderly's exercise participation and their satisfaction with instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Especially, because older people are at risk of developing multimorbid conditions, which can lead to various physical and mental health problems including cognitive decline in late life if left untreated. Previous studies have found several factors that can promote the mental health of aging adults, including spiritual comfort services ( 82 ), and tailored physical activity programs ( 83 , 84 ). This study complements previous findings in highlighting the importance of self-efficacy, and social support as lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, because older people are at risk of developing multimorbid conditions, which can lead to various physical and mental health problems including cognitive decline in late life if left untreated. Previous studies have found several factors that can promote the mental health of aging adults, including spiritual comfort services ( 82 ), and tailored physical activity programs ( 83 , 84 ). This study complements previous findings in highlighting the importance of self-efficacy, and social support as lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the age invariance paradox, older adults typically report a high level of well-being and life satisfaction while aging (Kanning & Schlicht, 2008). Physical activity is one of the key contributors of well-being, including self-worth, selfrespect, and a sense of social connectedness (Jung et al, 2023;Kanning & Schlicht, 2008;McAuley et al, 2004). Furthermore, engagement in physical activity interventions has been shown to counteract and reduce adverse health outcomes observed in older age (Auerswald et al, 2022;Wijsman et al, 2013), and according to estimates of the World Health Organization, "every dollar spent on physical activity promotion will save the healthcare system $3.2 in costs associated with providing medical care" (Andrieieva et al, 2019(Andrieieva et al, , p. 1312.…”
mentioning
confidence: 99%